FORMING AN INTERNATIONAL BRAND OF AN AGRICULTURAL COMPANY USING DIGITAL MARKETING: SYNGENTA’S EXPERIENCE - Bolotna, Oksana; Gliebova, Nataliia; Snitko, Anastasiia (Current Problems of Sustainable Development, 2026)
This scientific article examines the theoretical and practical frameworks for forming the international brand of an agricultural company through digital marketing communications, using the case of the transnational corporation Syngenta. Against the backdrop of global economic digitalization and intensifying international competition, the study argues that digital channels-including corporate web platforms, professional online communities, and specialized digital service solutions-have evolved from simple promotion tools into core elements of strategic management. These tools are now essential for positioning companies in the global market, building stakeholder trust, and strengthening international reputation. The methodological basis of the research includes a systems approach, strategic analysis, and content analysis of Syngenta’s digital infrastructure (specifically the syngenta.ua portal). The authors identify three primary blocks of digital communication: product-informational, service-digital, and interactive-communicative. A significant finding is that Syngenta has successfully transitioned from a traditional transactional marketing model to a platform-based interaction model. By offering digital agronomic solutions like Cropwise Operations, Seed Selector, and Interra Scan, the brand becomes an integral part of the customer’s operational infrastructure. This integration creates a “strategic lock-in” effect, where the costs of switching to a competitor increase because the client is embedded in the company’s digital ecosystem. From a strategic management perspective, the article proves that digital marketing communications function as a VRIO resource (Valuable, Rare, Inimitable, and Organized), providing long-term competitive advantages through differentiation. The study highlights that Syngenta’s digital architecture facilitates a “global standardization – local adaptation” strategy. This approach ensures a unified corporate identity across more than 90 countries while remaining relevant to local agronomical and regulatory conditions. The research further systematizes the functional impact of digital tools into five key strategic roles: informational (transparency), interactive (stakeholder engagement), reputational (trust building), analytical (data-driven decisions), and competitive (differentiation). The authors conclude that integrating digital marketing into the strategic management system enhances international competitiveness by reinforcing cognitive trust and expert legitimacy in the B2B segment. These findings provide a scalable model for other agricultural enterprises aiming to institutionalize innovation and improve brand equity in the global arena.